The influence of workforce agility and perceived organizational support on adaptive performance at public organizations manpower sector - Kusuma, Muhammad Eko Abrian; Wardoyo, Bambang; Nurliawaty, Nita (Institute of Computer Science (IOCS), 2025)
Adaptive performance is crucial for boosting the performance of public organizations. The Ministry of Manpower (Kemnaker), as the leading public organization responsible for the employment sector, needs to improve organizational governance and human resource adaptability to address the challenges of current environmental changes. This study aims to determine the role of workforce agility and perceived organization support on adaptive performance at public sector organizations in the manpower sector. The research method used was quantitative, with data collection through a survey. The population in this study was all civil servants (ASN) in the Ministry of Manpower of the Republic of Indonesia, using a purposive sampling technique, involving 93 respondents. Data analysis used IBM SPSS 25 software. The results of the regression analysis show that simultaneously, workforce agility and perceived organizational support have a significant effect on adaptive performance, with the calculated F value > F table and significance < 0.05. Partially, workforce agility (p = 0.000) has a significant effect on adaptive performance, while perceived organizational support (p = 0.069) does not show a direct significant effect. These findings indicate that employee work agility is a key factor in encouraging adaptability in manpower public organizations.